Usage Media Concrete for Increase Understanding Material on Force, Motion, and Energy for Elementary School Students - Indahsah, Siti; Gomulia Oscar (Riviera Publishing, 2025)
This study aims to describe the use of concrete media to improve students' understanding of force, motion, and energy concepts in elementary school. Concrete media such as toy cars, wooden blocks, springs, and magnetic objects were used to provide hands-on learning experiences, allowing students to observe real physical phenomena. This study employed a library research method. The results show that the use of concrete media increases student engagement, helps them understand the relationship between force and motion, and clarifies energy changes in various situations. Students' comprehension improved significantly, as shown in the evaluation results of each cycle. Therefore, the use of concrete media is highly effective in helping elementary school students understand basic science concepts, particularly those related to force, motion, and energy.